Correlation Effects of Near-Field Seismic Components in Circular Metro Tunnels: A Case Study—Tehran Metro Tunnels - Seyed Amin Razavian Amrei; Reza Vahdani; Mohsen Gerami; Gholamreza Ghodrati Amiri (Shock and Vibration)
Seismic evaluation of underground structures such as tunnels requires nonlinear dynamic analysis, due to the complex dynamic behavior of soil and the interaction of soil and structure. Simulation of the seismic response of the structure using nonlinear dynamic analysis is possible only with proper acceleration time history. Considering the vertical component of the earthquake (such as near-fault earthquakes) on the site is an important factor to achieve real structural responses. In the current study, soil-tunnel system has been modeled in ABAQUS software, considering Mohr–Coulomb nonlinear model for soil and concrete damage plasticity model for tunnel lining. In order to investigate the effect of seismic components correlation under different combinations of loads on the acceleration, axial force, and maximum shear force in tunnel lining, nonlinear dynamic analysis has been performed under four near-field earthquakes with different horizontal and vertical component ratios, considering 15 load combinations. The results show that increasing the vertical-horizontal component ratio has an insignificant effect on the maximum horizontal acceleration experienced by the tunnel lining. Also, the results of axial forces and shear forces indicate that increasing the ratio of vertical to horizontal components of the earthquake is the most effective factor on the axial force response.